Do accurate earnings forecasts facilitate superior investment recommendations? - LOH, Roger (Institutional Knowledge at Singapore Management University, 2006)
We find that analysts who issue more accurate earnings forecasts also issue more profitable stock recommendations. The average factor-adjusted return associated with the recommendations of analysts in the highest accuracy quintile exceeds the corresponding return for analysts in the lowest accuracy quintile by 1.27% per month. Our findings provide indirect empirical support for valuation models in the accounting and finance literatures (e.g., Ohlson, 1995) that emphasize the role of future earnings in predicting stock price movements. Our results also suggest that imperfectly efficient markets reward information gatherers, such as security analysts, for their costly activities in generating superior earnings forecasts.